Efficacy of AS04-Adjuvanted Vaccine Against Human Papillomavirus (HPV) Types 16 and 18 in Clearing Incident HPV Infections: Pooled Analysis of Data From the Costa Rica Vaccine Trial and the PATRICIA Study. (5th September 2020) - Tota, Joseph E; Struyf, Frank; Hildesheim, Allan; Gonzalez, Paula; Ryser, Martin; Herrero, Rolando; Schussler, John; Karkada, Naveen; Rodriguez, Ana Cecilia; Folschweiller, Nicolas; Porras, Carolina; Schiffman, Mark; et al.
Abstract: Clinical trial data and real-world evidence suggest that the AS04-adjuvanted vaccine targeting human papillomavirus types 16 and 18 (AS04-HPV-16/18) vaccine provides nearly 90% protection against cervical intraepithelial neoplasia grade 3 or higher irrespective of type, among women vaccinated before sexual debut. This high efficacy is not fully explained by cross-protection. Although AS04-HPV-16/18 vaccination does not affect clearance of prevalent infections, it may accelerate clearance of newly acquired infections. We pooled data from 2 large-scale randomized controlled trials to evaluate efficacy of the AS04-HPV-16/18 vaccine against clearance of nontargeted incident infections. Results of our analysis do not suggest an effect in expediting clearance of incident infections. Abstract : The AS04-adjuvanted vaccine targeting human papillomavirus types 16 and 18 does not affect clearance of prevalent infections but may accelerate clearance of new infections. Our results, including data from 2 randomized controlled trials, suggest no expedited clearance of incident infections